Law No. 11 Of The Year 2013 On The Amendment Of Some Provisions Of The Income Tax Law Promulgated By Law No. 91 Of The Year 2005 And Amendments Thereof As Amended By The Decree-Law No. 101 Of The Year 2012 = قانون رقم 11 لسنة 2013 بشأن تعديل بعض أحكام قانون الضريبة على الدخل الاصدر بالقانون رقم 91 لسنة 2005 وتعديلاته والمعدل بالقرار بقانون رقم 101 لسنة 2012 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.